Pancreatic pseudocyst development due to organophosphate poisoning - M. M. Murat HARPUTLUOĞLU,; Ulvi DEMİREL,; Hakan ALAN,; Fehmi ATEŞ,; Murat ALADAĞ,; Melih KARINCAOGLU,; Fatih HİLMİOĞLU, (Turkish Journal of Gastroenterology, 2019)
-